(untitled) (The Review of Diabetic Studies, 2025)
Background: Mobile health (mHealth) applications are increasingly employed to support the management of chronic illnesses in pediatric populations. They provide opportunities for improved adherence, enhanced self-management, and better integration of care between patients, caregivers, and clinicians. Objective: This systematic review aimed to synthesize the evidence regarding the feasibility, effectiveness, and limitations of mHealth applications for managing chronic conditions in children and adolescents. Methods: Peer-reviewed studies published between 2012 and 2025 were reviewed, encompassing randomized controlled trials, cohort studies, feasibility pilots, and cross-sectional investigations. A total of 17 studies met the inclusion criteria, covering chronic illnesses such as diabetes, asthma, epilepsy, cystic fibrosis, obesity, kidney disease, hematological disorders, and pulmonary conditions. Results: The findings demonstrated significant improvements in treatment adherence, glycemic control, quality of life, and patient satisfaction across multiple conditions. Notably, randomized controlled trials in diabetes and obesity showed reductions in HbA1c and BMI, while interventions for epilepsy and iron chelation improved medication compliance. mHealth interventions also supported psychosocial well-being, including reduced procedural anxiety and improved caregiver–patient communication. However, heterogeneity in intervention design and methodological limitations restricted cross-study comparability. Conclusions: mHealth applications hold promise as adjunctive tools for pediatric chronic illness management. They enhance self-management and clinical outcomes but require further standardization, large-scale validation, and integration into health systems to maximize impact.